Overexpression of PTPRCAP inhibits biological function of lung adenocarcinoma through apoptosis pathway - Yuting Yang; Baoshan Zhao; Yingjie Jiang; Xiaoli Han; Jingtao Huang; Guangrui Sun; Zongying Liang (PLoS ONE, 2025)
Background PTPRCAP (protein tyrosine phosphatase receptor C-associated protein) has been implicated in tumor suppression in several malignancies; however, its role in lung adenocarcinoma (LUAD) remains unclear. This study aimed to investigate the expression profile and functional significance of PTPRCAP in LUAD. Methods Forty-five pairs of LUAD and adjacent non-tumor tissues were collected from patients undergoing surgery at Chengde Medical University Affiliated Hospital. PTPRCAP mRNA and protein levels were quantified by RT-qPCR and immunohistochemistry (IHC), respectively, and correlated with clinicopathological features. A549 and H1299 LUAD cell lines and BEAS-2B normal bronchial epithelial cells were used for in vitro assays. PTPRCAP was overexpressed via plasmid transfection (OE group) and compared with vector-transfected controls (Vector group). Functional assays included CCK-8 proliferation, scratch wound healing, Transwell migration/invasion, and Annexin V-PE apoptosis assays. Apoptosis-related proteins (Bax, Bcl-2, and cleaved caspase-3) were evaluated by Western blot. The effect of overexpression PTPRCAP on tumor growth was observed through nude mouse xenografts. Results PTPRCAP mRNA and protein levels were significantly lower in LUAD tissues than in adjacent non-tumor tissues (P < 0.05). Low PTPRCAP expression correlated with advanced TNM stage and poor differentiation (P < 0.05). In vitro, PTPRCAP expression was markedly reduced in A549 and H1299 cells compared with BEAS-2B. Overexpression of PTPRCAP significantly suppressed proliferation, migration, and invasion (P < 0.001), and increased apoptosis rates in both cell lines (P < 0.01). Mechanistically, PTPRCAP upregulation elevated pro-apoptotic Bax and cleaved caspase-3 while downregulating anti-apoptotic Bcl-2 (P < 0.05). In vivo xenograft experiments demonstrated that overexpression PTPRCAP inhibited tumor growth in nude mice (P < 0.001). Conclusions PTPRCAP is downregulated in LUAD and acts as a tumor suppressor by promoting apoptosis and inhibiting proliferation, migration, and invasion. These findings suggest PTPRCAP as a potential therapeutic target for LUAD.